Effect of graphene oxide interlayer electron-phonon coupling on the electro-optical parameters of a ferroelectric liquid crystal. Issue 21 (21st February 2017) - Singh, D. P.; Kumar, V.; Kumar, A.; Manohar, R.; Pasricha, Renu; Duponchel, B.; Boussoualem, Y.; Sahraoui, A. H.; Daoudi, A.
Abstract : Electro-optical properties of FLC are cell thickness dependent. Interlayer electron-phonon coupling is responsible for the change in the E-O properties. The FLC–GO composite is suitable for use in UV filters. Abstract : A small concentration of graphene oxide (GO) was dispersed in ferroelectric liquid crystal (FLC), and the effect of the same on the electro-optical parameters of the FLC–GO composite has been investigated using various techniques, such as Raman spectroscopy, UV-visible absorbance, XRD, and polarizing optical microscopy. The electro-optical parameters were remarkably modified and this effect is found to be strongly dependent on the cell thickness. Interlayer electron-phonon coupling and relative orientation between GO and the director of FLC are responsible for these effects. The presence of GO mainly induces local orientation in the FLC molecules at the interface, which was confirmed by X-ray diffraction results. The change in the UV absorbance of the composite is mainly due to scattering of incident photonic radiation through GO, smectic layers, and multi-domains. This study demonstrates optimization of the cell thickness in case of nanomaterials dispersed in mesogenic systems for their device applicability, such as UV light filters, and for the tailoring of material parameters by varying the cell thickness.